Olefin metathesis : theory and practice - Grela, Karol, 1970- (Hoboken, New Jersey : Wiley, 2014)
This is a complete examination of the theory and methods of modern olefin metathesis, one of the most widely used chemical reactions in research and industry. Provides basic information for non-specialists, while also explaining the latest trends and advancements in the field to experts. Discusses the various types of metathesis reactions, including CM, RCM, enyne metathesis, ROMP, and tandem processes, as well as their common applications. Outlines the tools of the trade-from the important classes of active metal complexes to optimal reaction conditions.
Chapter 7: Olefin Metathesis Polymerization7.1 Introduction; 7.2 ROMP-The Mechanism; 7.3 The Initiators/Catalysts; 7.4 ROMP-The Monomers; 7.5 ROMP-Applications; 7.6 Acyclic Diene Metathesis; 7.7 Cyclopolymerizations; 7.8 Conclusions; References; Section 3: Applications of Olefin Metathesis Reactions; Chapter 8: Applications in the Synthesis of Natural and Biologically Active Molecules; 8.1 Introduction; 8.2 Ring-Closing Metathesis (RCM); 8.3 Relay Ring-Closing Metathesis (RRCM); 8.4 Temporary Tether and RCM (TT-RCM); 8.5 Cross-Metathesis (CM); 8.6 Ring-Opening Metathesis (ROM)
"Zespol III."
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Metathesis (Chemistry); Catalysis; Alkenes; SCIENCE -- Chemistry -- Organic; Alkenes; Catalysis; Metathesis (Chemistry); Electronic books; Electronic books